Guidelines for Analyzing Bearing Capacity and Embedded Length of Rock-Socketed Piles in Moderately Weathered Granite - srikongsri, atitep; Saelee, Pongsak (Srinakharinwirot University Engineering Journal, 2024)
Bearing capacity of pile socketed in moderately weathered granite was statically analyzed using FHWA and Tomlinson methods. The capacity equations for the pile socket including friction and tip resistance were based on several geotechnical parameters such as type of rock, rock quality designation (RQD), degree of weathering, and compressive strengths of rock and concrete. Two bored piles with a diameter of 0.80 m and 1.00 m were selected for analysis. Calculated results of the methods are then compared. The results show that the friction resistances yielded from both methods are comparable, however, the tip resistance of Tomlinson method exhibits much higher the magnitude than FHWA. The results were also validated by static pile load test results. Comparison between the calculated results and the maximum tested loads implies an ample factor of safety. Therefore, an analytical approach for effective socket depth is proposed herein to reduce the embedded length in rock for yielding appropriate values of factor of safety.